Aspek Hukum Wanprestasi Selebgram Terhadap Usaha Bisnis Online dan Upaya Perlindungan - Annisa Chaerani; Taun Taun (Jurnal Ilmiah Wahana Pendidikan, 2022)
The legal aspect is a rule that is in charge of regulatingeverything regarding the norms of the implementation oftrade, financial, industrial activities that are associatedwith production, services, exchange of goods usingmoney. And the online business itself is very inherentamong the people of Indonesia. In addition, onlinebusiness is very popular, especially for teenagers inIndonesia, and there are many celebgrams who openservices for endorsements, the selegram itself is seenfrom how many instagram or other social mediafollowers they have The more followers/ followersowned by the celebgram, the higher the cost ofendorsement services will be. Not only legal protectionefforts for consumers or called consumer protection butin the current era, many business people or onlinebusinesses also need these legal protection efforts.